MODEL OF SYMBIOTIC INFORMAL BUSINESS NETWORK BASED ON SERVICES OF FUNCTIONALLY DEPENDENT BUSINESS UNITS - O. Gabdrakhmanov (Publishing House of the State University of Management, 2018)
The author identifies the methods of creating and defines a model of sym-biotic informal business networks for the purpose of reciprocal exchange of resources, works and services, which allows the participants to solve their activity problems saving substantial amounts of money and reducing costs. The essence of informal business net-works is analysed in the context of the theoretical and methodological approach to the more general concept of the informal economy, which has been in considerable demand in research in recent years. The research findings might be helpful to management and economics experts dealing with the problems of increasing the eficiency in modern con-ditions for researching theoretical and practical management.